Digital Transformation of Financial and Marketing Management as a Strategic Innovation for Home Industries in Supporting Sustainable Economic Growth in Tolitoli Regency - Ilham Rahim; Mardiana Mardiana (FEB Universitas Mulawarman, 2025)
(Problem) Despite relatively high ownership of digital devices, the effective utilization of financial applications and digital marketing strategies among business actors is still low. (Novelty) Unlike prior studies that separately examine digital finance or marketing adoption, this study develops an integrated model combining both aspects into a unified digital platform. The novelty lies in contextualizing digital readiness assessment for local entrepreneurs in Tolitoli, identifying specific barriers and opportunities, and proposing a simple, adaptive, and user-friendly digital system that addresses their real conditions. This research thus contributes not only to academic discourse but also to the formulation of local economic policy and the roadmap for home industry digital transformation. (Methods) This research applies a mixed-method design, combining a quantitative survey of 40 home industry actors with qualitative insights obtained from in-depth interviews and Focus Group Discussions (FGD). The analysis incorporates descriptive statistics and SWOT analysis to identify readiness levels, opportunities, and constraints. (Results) The digital readiness index reached 56.7% (moderate), with device ownership at 82% (high). However, the use of financial applications (42.5%) and social media marketing (40%) remained low, revealing a capability gap. SWOT analysis shows strengths in unique local products and strong social capital, weaknesses in digital literacy and reliance on traditional marketing, opportunities from e-commerce growth and government programs, and threats from external competitors with faster digital adoption. (Conclusion) Digital transformation can enhance operational efficiency, market reach, and competitiveness of home industries. The study proposes the development of an integrated digital platform tailored to local conditions, aligning with OECD recommendations for gradual, context-based digitalization.